Practice of Mechanical Ventilation in the Intensive Care Unit of the Reference Hospital in Maradi: A Descriptive and Retrospective Study of the First Three Years of Activity - Maikassoua Mamane; Abdoulaye Maman Bachir; Alassane M. Bachir; Hassane M. Laoul; Hamissou S. Nourya; Magagi Amadou; Adakal Ousseini; James D. Lasaye; Chaibou M. Sani; Boukari M. Baoua (European Scientific Journal, ESJ, 2026)
Introduction: Mechanical ventilation (MV) is a technique that assists or replaces breathing using a device called a ventilator or artificial respirator. The aim of this study was to evaluate the practice of mechanical ventilation in the intensive care unit of the Maradi referral hospital. Methodology: This was a descriptive, cross-sectional, retrospective study covering a three-year period from July 1, 2021, to June 30, 2024, conducted in the intensive care unit of Maradi Referral Hospital, focusing on patients who underwent mechanical ventilation. Results: During the study period, 133 patients out of a total of 489 were recorded with an MV frequency of 27.19%. The average age was 40.79±19.25 years (range 4 to 87 years) with a sex ratio of 3.29 in favor of males. Invasive ventilation was more commonly used (99%) than NIV, with the main indications being disorders of consciousness (47.4%), followed by respiratory distress (29.3%). Volumetric mode was used more than barometric mode (84% vs. 16%). Sedation-analgesia was necessary in 98% of patients and consisted mainly of midazolam and fentanyl. The average duration of ventilation was 6±5.3 days. Ventilator-associated pneumonia (VAP) was the main complication associated with mechanical ventilation (89.5%). The mortality rate was 77%. Conclusion: Mechanical ventilation is increasingly common in our department, with a high mortality rate. It is mainly indicated for severe head injuries.